Professional Development Needs for General Education Teachers to Educate Children with Autism Spectrum Disorders - Natalie Precise; Kim Finch; Cynthia Macgregor (The Advocate, 2018)
The purpose of this study was to identify areas in which educational leadership could aid in preparing general education teachers to educate children with Autism Spectrum Disorders (ASD). A needs assessment was conducted through a case study in a rural Missouri school district to identify the level of efficacy noted by teachers of various experience levels. Pre-service preparation and provided professional development were examined to identify ways in which educational leaders could further the knowledge base and effectiveness of general education teachers to teach students with ASD.